Transcriptional analysis of the intestinal mucosa of patients with ulcerative colitis in remission reveals lasting epithelial cell alterations - Planell, Núria; Lozano, Juan J; Mora-Buch, Rut; Masamunt, M Carme; Jimeno, Mireya; Ordás, Ingrid; Esteller, Miriam; Ricart, Elena; Piqué, Josep M; Panés, Julián; Salas, Azucena (Gut, 2013)
Objective Ulcerative colitis (UC) is a chronic condition characterised by the relapsing inflammation despite previous endoscopic and histological healing. Our objective was to identify the molecular signature associated with UC remission. Design We performed whole-genome transcriptional analysis of colonic biopsies from patients with histologically active and inactive UC, and non-inflammatory bowel disease (non-IBD) controls. Real-time reverse transcriptase-PCR and immunostaining were used for validating selected genes in independent cohorts of patients. Results Microarray analysis (n=43) demonstrates that UC patients in remission present an intestinal transcriptional signature that significantly differs from that of non-IBD controls and active patients. Fifty-four selected genes were validated in an independent cohort of patients (n=30). Twenty-nine of these genes were significantly regulated in UC-in-remission subjects compared with non-IBD controls, including a large number of epithelial cell-expressed genes such as REG4, S100P, SERPINB5, SLC16A1, DEFB1, AQP3 and AQP8, which modulate epithelial cell growth, sensitivity to apoptosis and immune function. Expression of inflammation-related genes such as REG1A and IL8 returned to control levels during remission. REG4, S100P, SERPINB5 and REG1A protein expression was confirmed by immunohistochemistry (n=23). Conclusions Analysis of the gene signature associated with remission allowed us to unravel pathways permanently deregulated in UC despite histological recovery. Given the strong link between the regulation of some of these genes and the growth and dissemination of gastrointestinal cancers, we believe their aberrant expression in UC may provide a mechanism for epithelial hyper-proliferation and, in the context of malignant transformation, for tumour growth.